2020
DOI: 10.3390/ijgi9040200
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Heritage and the Shaping of Tourist Itineraries in Rural Areas: The Case of Historical Ensembles of Extremadura, Spain

Abstract: Heritage is a very complex concept that is characterized by having multiple meanings. Despite this, there is no doubt as to its attraction for carrying out tourist activities. In the specific case of cultural heritage, there is widespread agreement in considering it as a tourist resource given the interest it raises amongst visitors of all origins. This is not, however, always the case and it can be observed that in certain areas, especially rural ones, certain limitations exist. They are caused by multiple fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The presence of camping sites and youth hostels with many places also generates many jobs (cleaning, leisure, catering in the accommodation) and a high number of overnight stays because they tend to be more occupied in the summer seasons [65,66]. This produces greater positive effects than other types of accommodation such as rural houses, more family-run businesses with fewer places and complementary offers, and hotels that are not so in demand in these natural enclaves, as tourism in greater contact with nature is preferred [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of camping sites and youth hostels with many places also generates many jobs (cleaning, leisure, catering in the accommodation) and a high number of overnight stays because they tend to be more occupied in the summer seasons [65,66]. This produces greater positive effects than other types of accommodation such as rural houses, more family-run businesses with fewer places and complementary offers, and hotels that are not so in demand in these natural enclaves, as tourism in greater contact with nature is preferred [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [13] studied tourism services distribution channels in Hanoi, Vietnam, using network measures (density, clustering coefficient, and closeness centrality) and organizational risk analysis to study the relations between travel agencies and tour operators based on their online presence and identified patterns of the information flows in the network. On the other hand, other studies [14][15][16][17][18][19][20][21] are also interested in tourists' perception of a destination. Toward this direction, relevant papers analyze the nature of the linkages of nodes in tourist attraction networks of travel destinations, with most of the cases studied so far located in Asia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building on GIS network analysis, they investigated the spatial differences in reaching the attractions by car, public transport, and bike and proposed strategies in tourism development in Beijing suburban area. The authors of [19] studied a network of historical ensembles in Extremadura, Spain, to contribute to tourism planning in the context of creating thematic (expressing a peculiar kind of resource) tourist itineraries. The study showed the potential of generating tourist itineraries as a first step in the design of tourist products and highlighted the utility of network analysis as a management tool of a coherent and efficient tourist policy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Heritage has a complex meaning, which includes tangible and intangible elements defining time and space that can be associated with culture and nature. Through tourism, cultural heritage can be transformed into an important resource for local economic development [ 1 ]. With the growing demand for experiential cultural tourism (in which tourists can experience country-side life, can learn local traditions, crafts, etc.…”
Section: Introductionmentioning
confidence: 99%